Cyanobacteria cell prediction using interpretable deep learning model with observed, numerical, and sensing data assemblage. (15th September 2021) - Pyo, JongCheol; Cho, Kyung Hwa; Kim, Kyunghyun; Baek, Sang-Soo; Nam, Gibeom; Park, Sanghyun
Highlight: Data nexus was prepared from in-situ, synthetic measurement, and remote sensing data. Convolutional attention model was designed to predict cyanobacteria cells. Attention network delivered the importance of Chlorophyll-a map for the prediction. Convolutional attention model was feasible to harmful algae with data assemblage. Abstract: Massive cyanobacterial blooms in river water causes adverse impacts on aquatic ecosystems and water quality. Complex and diverse data sources are available to investigate the cyanobacteria phenomena, including in situ data, synthetic measurements, and remote sensing images. Deep learning attention models can process these intricate sources to forecast cyanobacteria by identifying important variables in the data sources. However, deep learning attention models for predicting cyanobacteria have rarely been studied using an assemblage of various datasets. Thus, in this study, a convolutional neural network (CNN) model with a convolutional block attention module (CNNan ) was developed to predict cyanobacterial cell concentrations by using the observed cell data from field monitoring, chlorophyll-a distribution map from hyperspectral image sensing, and simulated water quality outputs from a hydrodynamic model. Then, the prediction performance of the CNNan model was compared to an environmental fluid dynamics code (EFDC) simulation and a CNN model without an attention network. The seasonal variations of the predicted cyanobacteria that was obtained from CNNan showed the best agreement with the observed variations with Nash–Sutcliffe efficiency values higher than 0.76 when compared to the EFDC and CNN predictions. The daily hydrodynamic outputs allowed the prediction of cyanobacteria cells, while the rich information of the chlorophyll-a map contributed to the improvement of the prediction performance at certain periods. Moreover, the attention network visualized the importance of the additional chlorophyll-a map and improved the CNNan model prediction performance by refining the input features. Therefore, this study demonstrated that a deep learning model with data assemblage is practically feasible for predicting the presence of harmful algae in inland water. Graphical abstract: Image, graphical abstract